Perfil dos pesquisadores PQ do CNPQ da área de Engenharia de Produção - Kodama, Celso Minoru Higa [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
There is a need for ongoing evaluation of the researchers not only engineering and production in all areas of knowledge engineering. To check the quality and veracity of scientific production, the CNPq is a brazillian government agency designed to evaluate researchers, classify them and give the encouragement and incentive for their research. This study quantifies the CNPq researchers in the field of Production Engineering according to the time of operation in research, number of guidelines for masters and doctoral, number of articles in national and international journals or magazines and congresses. The classification of these researchers, according to the proposed quantification, is confronted with the level of research they have in CNPq. The researcher starts his career at level 2, after it spending levels for 1D, 1C, 1B reaches to the highest level 1A. The main conclusion to be drawn from this study is that excellent researchers with a significant number of guidelines, bitter years in the early levels because of the rules of the CNPq which only allows a researcher to achieve the highest levels after many years of research

Há uma necessidade de avaliação constante dos pesquisadores não só de engenharia de produção como em todas as áreas de conhecimento da engenharia. Para verificação da qualidade e veracidade da produção científica, o CNPq é um órgão governamental encarregado de avaliar os pesquisadores, classificá-los e dar o fomento e incentivo às suas pesquisas. Este trabalho quantifica os pesquisadores do CNPq da área de Engenharia de Produção segundo, o tempo de atuação em pesquisa, número de orientações de mestrado e doutorado, número de artigos em periódicos nacionais e internacionais e em congresos. A classificação destes pesquisadores, segundo a quantificação proposta, é então confrontada com o nível que estes possuem junto ao CNPq. De acordo com esta entidade, o pesquisador inicia a carreira no nível 2, e após passar pelos níveis 1D, 1C, 1B até atingir o nível mais alto 1A. A principal conclusão que se tira deste estudo é a de que excelentes pesquisadores com número significativo de orientações, amargam anos nos níveis iniciais por conta das regras do CNPq que só permite um pesquisador atingir os níveis mais altos após muitos anos de pesquisa
Keywords: Engenharia de produção; Pesquisadores - Avaliação; Produtividade; Avaliation; Researchers; Industry Engeneering